Tuberculose na população em situação de rua do município de Aracaju/SE (2019 a 2022) - Avelino, Maria de Lourdes Barros (2023)
This work aimed to identify the prevalence of tuberculosis in the homeless population in Aracaju between 2019 and 2022, based on a survey carried out in institutional sites. The research developed was descriptive, based on qualitative and quantitative data, resorting to the research procedures of literature review on the themes addressed and data collection through documentary research on the sites of the Ministry of Health, the Information System of Notifiable Diseases (SINAN), and the Secretary of Health of Aracaju. The research analysis is guided by the historicaldialectical materialist method, due to the possibility of critical apprehension of reality phenomena. The study, therefore, outlined an overview of the configuration of social policy in capitalist society and its consequences for the most vulnerable segments; described the sociodemographic profile of homeless people in Aracaju; and verified the relationship between the prevalence of Tuberculosis cases in the homeless population of Aracaju and the context of restriction of rights in which they are subjected, comparing with the general occurrence of cases of the disease in the municipality. Aracaju registered 2081 cases of Tuberculosis on SINAN from 2019 to 2022, 4.2% of which were PSR and 1.4% were ignored/blank. The sociodemographic profile of HP with tuberculosis is made up of males (85.2%), black/brown (82.9%), aged 25 to 44 years (59%), and a predominance of new cases (53%) and re-entry after treatment abandonment (34%), pulmonary type (98%), high rate of alcoholics (73.8%), smokers (67%), users of illicit drugs (65.9%), with closure due to cure (27.2%) and treatment abandonment (25%). The hypothesis that the cure rate against tuberculosis in PSR is reduced compared to the general population that presents the disease was confirmed. More research is needed to support and expand discussions about tuberculosis and HP, to make the public health problem visible and support decisions for the implementation of social policies by the State.